MATHEMATICAL MODELS OF A REQUIRED POWER DESIGN FOR IRRIGATION WITH SMALL-SIZED ELECTRIC MOTORS - Gabriel Filho, L. R. A.; Vérri, J. A.; Putti, F.F.; Cremasco, C. P.; Silva, A. O.; Seraphim, O. J.; Halmeman, M. C. R.; Caneppele, F. L. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Irrigation methods in rural areas usually consist of pumping water from dams and reservoirs by engines connected to the electric power station or powered with diesel oil. Current assay establishes mathematical models for scaling low-power electric motors for irrigation in small cultivated areas. Equations of engine power were determined by numerical integration and by the theorem of kinetic energy. A geometric model was established with a paraboloid of revolution to determine the volume of the reservoir. A 3600 m² area was irrigated during 4 h, 380 m distant from the dam, with a 21° slope, for simulation purposes. The amount of water for irrigation was 5 U m² by means of a dam with diameter 14 m and 5 m deep. The establishment of mathematical models scaled up a 2.5 hp engine with a removal of 5000 L of water from a 385 000 L dam, with a variation of 7.2 cm and the immersion of the engine below this borderline.